Determinants of teachers' ICT acceptance in Jember Schools, Indonesia: a cross-sectional survey - Nur, Abdul Hamid Busthami; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (2013)
The study was a cross-sectional survey of factors that affected teachers’ use of ICT in Jember schools, Indonesia. The sample consisted of 1,137 teachers randomly selected from all of the SMAs, SMPs and SMKs in the district. A self-developed questionnaire based on an extended Technology Acceptance Model (e-TAM) measuring five hypothesized determinants of ICT acceptance, i.e. perceived usefulness, perceived ease of use, intention to use, computer self-efficacy and organizational support, was administered to the respondents with the help of Dispendik and school principals. Results of Structural Equation Modeling (SEM) applied on the data revealed all five constructs (perceived usefulness, perceived ease of use, intention to use, computer self-efficacy and organizational support) to be statistically significant determinants of Jember teachers’ ICT acceptance. The hypothesized SEM model fitted the data adequately, accounting for approximately 63% of the variance explained. The structural model also produced a statistically significant change in the chi-square value when tested across gender, indicating that gender influenced teachers’ acceptance of ICT. The findings have important implications for stakeholders and policy makers, particularly with respect to their efforts to galvanize greater ICT utilization among teachers in Indonesian schools.